PERAN PENDAPATAN ASLI DAERAH DALAM MENUNJANG DESENTRALISASI FISKAL DAN PEMBANGUNAN DAERAH (Studi Badan Pendapatan Daerah Provinsi Sumatera Barat) - Rahmatul Putra, Nanda; Frinaldi, Aldri; Magriasti, Lince (Sustainability (STPP) Theory, Practice and Policy, 2023)
Supporting Local Revenue in Fiscal Decentralization and Regional Development (The Study in The Departement of Revenue at Provinsi Sumatera Barat). Regional governments are required to be able to regulate and manage their own households broadly and thoroughly based on applicable regulations and to develop and increase Local Own Revenue. This is in accordance with Law No. 32 of 2004 concerning regional government, in the framework of implementing regional autonomy. This study aims to identify, describe and analyze the role of local revenue in supporting fiscal decentralization and regional development. This study used a qualitative research method with a descriptive approach. The analytical method used is the interactive Miles and Huberman method. It can be concluded that the Regional Original Revenue of West Sumatra Province has a degree of fiscal decentralization which is categorized as sufficient. The level of dependency that is not so high indicates an adequate contribution to development financing in the West Sumatra Provincial government